Agribusiness, Corporate Social Responsibility, and Health of Agricultural Migrant Workers - Ortega, María Isabel; Sabo, Samantha; Aranda Gallegos, Patricia; De Zapien, Jill Eileen Guernsey; Zapien, Antonio; Portillo Abril, Gloria Elena; Rosales, Cecilia (Frontiers in Public Health, 2016)
Living conditions and health of migrant farmworkers could benefit from a health promotion model based on Corporate Social Responsibility (CSR). Objective. To understand how Mexican agribusiness owners and general managers view and practice CSR. Methods. We interviewed 8 agribusiness owners/managers and 233 farmworkers using open-ended interviews, and gathered anthropometrical data of 133 children from farmworkers families. To guide our analysis and discussion we followed the two dimension-model of CSR proposed by Quazi and O’Brien. Results. According to interviewee responses, mean percentage of agreement with CSR concept was 77.4%, with a range of 54 to 85.7%. Main health related issues among farmworkers were infectious diseases, crowding, and access to health care services; there were acute cases of undernutrition among farmworkers’ children and diets were of poor quality. Discussion. Agribusiness owners and managers understand and practice CSR according to a wide and modern view, which contradicts with farmworkers living conditions and health. Quazi and O'Brien model should consider the social context in which it is analyzed, and the social manifestations of community development as a tool for further analysis on the perceptions and actions of entrepreneurs.